The legacy of pluralism : the continental jurisprudence of Santi Romano, Carl Schmitt, and Costantino Mortati - Croce, Mariano; Goldoni, Marco (Stanford, California : Stanford University Press, 2021)
How should the state face the challenge of radical pluralism? How can constitutional orders be changed when they prove unable to regulate society? Santi Romano, Carl Schmitt, and Costantino Mortati, the leading figures of Continental legal institutionalism, provided three responses that deserve our full attention today. Mariano Croce and Marco Goldoni introduce and analyze these three towering figures for a modern audience.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 26, 2020).
Keywords: Romano, Santi, -- 1875-1947.; Schmitt, Carl, -- 1888-1985.; Mortati, Costantino; Legal polycentricity; Law; Jurisprudence & general issues; International law